Analyzing Halal Tourism Implementation Challenges and Opportunities in Siak District, Riau - Yudha Perwira; Zahra Almira (IHSA Institute, 2024)
Halal tourism, catering to the needs and preferences of Muslim travelers, has emerged as a significant market segment in the global tourism industry. This research focuses on the analysis of halal tourism implementation in Siak District, Riau, Indonesia. The study aims to evaluate the effectiveness of halal tourism practices, identify challenges, and explore opportunities for improvement in the region. Employing a mixed-methods approach, qualitative data were collected through semi-structured interviews with key stakeholders, while quantitative data were gathered through surveys administered to tourists visiting Siak District. The findings reveal several key insights: infrastructure development remains a challenge, cultural sensitivity is essential for preserving authenticity, marketing strategies need enhancement, halal certification standards require attention, and community engagement is crucial for sustainable development. Despite challenges, opportunities for improvement include diversifying tourism products, capacity building, and embracing sustainable practices. The implications of this research extend beyond Siak District, offering valuable insights for destinations worldwide seeking to tap into the growing market of halal tourism. By addressing challenges and capitalizing on opportunities, Siak District and destinations globally can enhance competitiveness, sustainability, and inclusivity in halal tourism offerings, fostering socio-economic growth and cultural preservation.